2020
DOI: 10.1101/2020.05.20.107664
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Homeostatic regulation of STING by Golgi-to-ER membrane traffic

Abstract: Coat protein complex I (COP-I) mediates the retrograde transport from the Golgi to the ER 1,2 . Mutation of the COPA gene, encoding one of the COP-I subunits (α-COP), causes an immune dysregulatory disease (COPA syndrome) 3 . The molecular mechanism by which the impaired retrograde transport results in autoinflammation is not understood. Here we report that STING 4 , an innate immunity protein, is a cargo of the Golgi-to-ER membrane transport. In the presence of the diseasecausative α-COP variants, STING canno… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…Therefore, retrograde transport of STING would require an adaptor protein. This hypothesis is supported by prepublication data from two laboratories, demonstrating that COPA binding to STING is dependent on Surfeit protein 4 (SURF4) (47,48). This also agrees with our proteomic analysis, where SURF4 and COPA were immunoprecipitated with STING after overexpression in HEK293T cells (Figure 2A).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, retrograde transport of STING would require an adaptor protein. This hypothesis is supported by prepublication data from two laboratories, demonstrating that COPA binding to STING is dependent on Surfeit protein 4 (SURF4) (47,48). This also agrees with our proteomic analysis, where SURF4 and COPA were immunoprecipitated with STING after overexpression in HEK293T cells (Figure 2A).…”
Section: Discussionsupporting
confidence: 91%
“…Meanwhile, recent insights from human genetic studies (see below) have unfolded a mechanism that operates at steady state and actively retrieves STING from the Golgi back to the ER to suppress cellular activation. Specifically, the adaptor protein SURF4 interacts with STING at the Golgi to facilitate STING’s encapsulation into COPI vesicles for retrograde transport 37 , 38 . Although future work needs to refine the molecular coordination of the intracellular destinations of STING, they appear to ultimately converge with STING’s degradation in lysosomes 39 .…”
Section: Overview Of the Cgas–sting Pathwaymentioning
confidence: 99%
“…Clinically, patients typically present with inflammatory arthritis, interstitial lung disease and kidney disease and exhibit a type I interferon signature in blood — features that are to some degree reminiscent of SAVI 132 . Recently, four independent studies have shown that defects caused by COPA mutations promote ligand-independent activation of STING-mediated signalling and that the elevated type I interferon signature associated with COPA dysfunction can be reduced by genetic or pharmacological interference with STING 37 , 38 , 133 , 134 . In a mouse model of COPA syndrome ( Copa E241K/+ ), type I interferon-driven inflammation was rescued by crossing these mice with STING-deficient ( STING gt/gt ) animals and, moreover, the embryonic lethality of homozygous Copa E241K/E241K mice was rescued by co-deletion of STING 37 .…”
Section: Activation Of Cgas–sting In Disease Contextsmentioning
confidence: 99%
“…All in all, the insight provided in Deng et al, 2020, Lepelley et al, 2020, Mukai et al, 2020, and Steiner et al, 2020 (Preprint) not only opens the door to novel treatment approaches for COPA syndrome, but it also advances understanding on the intricate mechanisms regulating STING activation and trafficking.…”
Section: Rivara and Ablassermentioning
confidence: 99%